Using The Heuristic Genetic Algorithm in Multi-runway Aircraft Landing Scheduling - Feng Xiao-rong; Feng Xing-jie; Zhao Rui (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Flights landing scheduling problem is an NP-hard problem, the article presents a heuristic genetic algorithm for multi-runway flights landing scheduling problem. The algorithm is based on a single chromosome coding and dynamic way flights runway allocation, then selects the center gene by the information entropy of each gene, and uses variation of the local search method to solve the slow convergence and easy to fall into local optimum of genetic algorithm. Compared with traditional genetic algorithm, the method can quickly give the better flight approach and landing order to reduce flight delays by the experimental results.  DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4488